Spatial analysis in primary health care utilization: a systematic review - Kharie, Mohamad Fadli; Juni, Muhamad Hanafiah; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Utilization is an important indicator for health service planning and can be determined through the count of actual usage of health services. There are also several determinants to health care utilization. This systematic review aims to explore the technical components from spatial analysis in primary health care utilization, the determinants frequently discussed, and the gap in the spatial analysis from these studies. Two databases were searched according to search strategy. A total of 15 articles were eligible. Each study was different in terms of analysis unit, spatial analysis, and utilization outcome. Spatial accessibility, sociodemographic, and geographical aspect were the frequent determinants discussed among the study of spatial utilization in this review. Several studies found the association between the determinants with utilization. However, spatial analysis in primary health care utilization studies still subjected to several limitation in term of their unit of analysis and source of data.